Modeling of AC Losses in High-speed PMSM Windings: Methods, Challenges, and Prospects - Kaiwei He; Wenxiang Zhao; Zhongze Wu; Jinghua Ji (CES Transactions on Electrical Machines and Systems)
High-speed permanent magnet synchronous motors (PMSMs) have recently been widely applied in various applications. However, due to the increased rotor speed and operating frequency increase, the winding AC losses rise substantially, posing risks to the safety operation. Accurate modeling of the AC losses has therefore become critical at the motor initial design stage. This paper reviews the main modeling methods for AC copper losses in PMSMs, including analytical methods, finite element methods, and hybrid modeling methods. The advantages and disadvantages of each method are analyzed in detail, and key issues in the modeling process are discussed. Finally, future research directions in AC copper loss modeling are explored, providing new insights for motor design and performance optimization.